2019
DOI: 10.1021/acs.molpharmaceut.9b00263
|View full text |Cite
|
Sign up to set email alerts
|

Berunda Polypeptides: Biheaded Rapamycin Carriers for Subcutaneous Treatment of Autoimmune Dry Eye Disease

Abstract: The USFDA-approved immunosuppressive drug rapamycin (Rapa), despite its potency, is limited by poor bioavailability and a narrow therapeutic index. In this study, we sought to improve bioavailability of Rapa with subcutaneous (SC) administration and to test its therapeutic feasibility and practicality in a murine model of Sjögren's syndrome (SS), a systemic autoimmune disease with no approved therapies. To improve its therapeutic index, we formulated Rapa with a carrier termed FAF, a fusion of the human cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 106 publications
5
16
0
Order By: Relevance
“…The clearance of the fusion protein was determined to be 0.28 mL/hr, which is consistent with other reported clearance of high molecular weight ELPs. 13,14 The volume of distribution was calculated to be 1.92 mL, which is consistent with the expected volume of blood in these mice. Bioluminescence images of spleen, kidneys, and liver showed that α-CD99-A192 nanoworms still resided in those organs 96 hours post-injection and accumulated at a higher level in the liver as compared to the spleen and kidney (p ≤0.05) (Representative bioluminescence images and quantification Fig.…”
Section: Pk Profile Of α-Cd99-a192 Nanoworms Fits the Biexponential Decay Modelsupporting
confidence: 74%
“…The clearance of the fusion protein was determined to be 0.28 mL/hr, which is consistent with other reported clearance of high molecular weight ELPs. 13,14 The volume of distribution was calculated to be 1.92 mL, which is consistent with the expected volume of blood in these mice. Bioluminescence images of spleen, kidneys, and liver showed that α-CD99-A192 nanoworms still resided in those organs 96 hours post-injection and accumulated at a higher level in the liver as compared to the spleen and kidney (p ≤0.05) (Representative bioluminescence images and quantification Fig.…”
Section: Pk Profile Of α-Cd99-a192 Nanoworms Fits the Biexponential Decay Modelsupporting
confidence: 74%
“…Therefore, the one-compartmental model was used to fit the plasma concentration–time curve. This model assumes that the whole body acts like a single uniform compartment, the drug is distributed instantaneously throughout the entire body, and drug elimination occurs immediately after the intravenous bolus injection. , …”
Section: Resultsmentioning
confidence: 99%
“…This model assumes that the whole body acts like a single uniform compartment, the drug is distributed instantaneously throughout the entire body, and drug elimination occurs immediately after the intravenous bolus injection. 53,54 Pharmacokinetic parameters are shown in Table 2. The distribution volume of control and Akt-in NPs was almost the same as the blood volume of a mouse.…”
Section: Effect Of Nanoparticles On Cell Viabilitymentioning
confidence: 99%
“…We envisage that new formulations of rapamycin will improve its efficacy for the treatment of DED. Lee et al proposed humanized bi-headed polypeptides for the subcutaneous delivery of rapamycin [ 65 ]. They applied this delivery system in the NOD mouse model of autoimmune dacryoadenitis, obtaining a beneficial reduction in lymphocytic infiltration in the lacrimal gland and levels of some pro-inflammatory cytokines in this tissue with no systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%